2000
DOI: 10.1002/9780470125922.ch2
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Strategy for Organic Photochemistry

Abstract: INTRODUCTION Modeling Photochemical ReactionsThe aim of this chapter is to provide an introduction to the practical computational investigation of photochemical reaction mechanisms. During the last decade or so, the speed of computers has grown considerably, and now the computational investigation of realistic models of organic compounds is becoming a standard practice. Current applications range from the investigation of the mechanism of synthetically useful reactions to the study of shortlived organic interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
134
0
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 205 publications
(145 citation statements)
references
References 105 publications
(209 reference statements)
3
134
0
8
Order By: Relevance
“…Subsequently, Michl 138 articulated this VB-based mechanism into a general photochemical model that highlighted the importance of ''funnels'' as the potential energy features that mediate the excited state species back into the ground state. Recent work by Bernardi et al 139 , Robb et al 140 showed that these ''funnels'' are conical intersections that can be predicted by simple VB arguments, and computed at a high level of sophistication. Similar applications of VB theory to deduce the structure of conical intersections in photoreactions were done by other groups.…”
Section: Concluding Remarks and Prospectivementioning
confidence: 99%
“…Subsequently, Michl 138 articulated this VB-based mechanism into a general photochemical model that highlighted the importance of ''funnels'' as the potential energy features that mediate the excited state species back into the ground state. Recent work by Bernardi et al 139 , Robb et al 140 showed that these ''funnels'' are conical intersections that can be predicted by simple VB arguments, and computed at a high level of sophistication. Similar applications of VB theory to deduce the structure of conical intersections in photoreactions were done by other groups.…”
Section: Concluding Remarks and Prospectivementioning
confidence: 99%
“…This involves locating critical points on ground and excited PESs as well as any seams of conical intersections between states. 1 Mechanisms of thermal reactions are traditionally described with the concept of a static reaction coordinate along a minimum energy path. In contrast, nonadiabatic mechanisms involve ultrafast processes and depend on changes in the kinetic energy in the energized system.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] The very concept of a conical intersection requires an adiabatic separation of time scales of two sets of degrees of freedom, which is naturally given in the electronic case via the Born-Oppenheimer approximation, but which is less common for vibrational transitions. 18,20,22,[33][34][35][36] In the context of vibrational conical intersections, an adiabatic separation has been introduced between high-frequency OH stretch and bend vibrations on the one hand, and lower-frequency backbone vibrations 28 or torsional modes 37,38 on the other hand within one molecule.…”
Section: Introductionmentioning
confidence: 99%